A Pigouvian Approach to Congestion in Matching Markets - Yinghua He; Thierry Magnac (Institute of Labor Economics (IZA), 2018)
Recruiting agents, or "programs" costly screen “applicants” in matching processes, and congestion in a market increases with the number of applicants to be screened. To combat this externality that applicants impose on programs, application costs can be used as a Pigouvian tax. Higher costs reduce congestion by discouraging applicants from applying to certain programs; however, they may harm match quality. In a multiple-elicitation experiment conducted in a real-life matching market, we implement variants of the Gale-Shapley Deferred-Acceptance mechanism with different application costs. Our experimental and structural estimates show that a (low) application cost effectively reduces congestion without harming match quality.
Keywords: D78; D47; D50; D61; I21; 330; Gale-Shapley Deferred Acceptance Mechanism; costly preference formation; screening; stable matching; congestion; matching market place